The Right to Be Oneself: The International and Italian Situation Regarding Gender Incongruence, Focusing on Legislation, Rights, Access to Care, and Appropriateness - Nicola Di Fazio; Giuseppe Delogu; Miriam Ottaviani; Gianpietro Volonnino; Mauro Arcangeli; Fabio Del Duca; Biancamaria Treves; Raffaele La Russa (Laws)
Gender incongruence is a current issue with implications in the legislative, social, and healthcare fields. In this context, misinformation is, at present, the main enemy of transgender rights equity. Over time, the scientific community has worked to reclassify this condition, removing it from psychiatric diagnoses. The method of our work involved investigating and comparing the different social and legislative measures adopted by various countries to ensure the rights and equality of individuals with gender incongruence. The result showed that there are various international approaches allowing adult and minor patients to access medical and administrative procedures for gender transition. In conclusion, there appears to be a need for international bioethical and legislative guidance in order to reduce and eventually eliminate the social inequalities faced by individuals with gender incongruence.